In vitro metabolism of copalic and kaurenoic acids in rat and human liver microsomes - Mauro, Mariana [UNESP]; da Silva, Rodrigo Moreira; de Campos, Michel Leandro; Bauermeister, Anelize; Lopes, Norberto Peporine; de Moraes, Natalia Valadares (Sociedade Brasileira de Quimica (SBQ), 2021)
Copalic (CA) and kaurenoic (KA) acids are the main diterpenes found in the oleoresin extracted from the copaiba tree (Copaifera sp). This study aimed to characterize the metabolism of CA and KA in rat and human liver microsomes using liquid chromatography with tandem mass spectrometry (LC-MS/MS). The in vitro assays showed deviations from the Michaelian kinetics in the metabolism of CA and KA. Putative metabolites of CA and KA were characterized by LC-MS/MS using electrospray ionization (ESI) with time of flight (LC-ESI-TOF) and ion-trap (LC-ESI-IT) systems and identified as a CA isomer and 16,17-dihydroxy-kaurenoic acid, respectively. CA and KA are subject to extensive metabolism with each passage through the liver with extraction ratios (E) estimated as 0.97 and 0.99, respectively. In conclusion, the kinetic parameters and metabolites described here might support drug development and the traditional use.
Keywords: Copaifera sp; Copalic acid; Kaurenoic acid; Liver microsomes; Metabolism